Garden therapy - Chris Ellis (South African Family Practice)
The world can be divided into two types of people. Outdoors people and Indoors people. In a similar way there are those of us who are gardeners and those who are not particularly interested in gardening or getting their hands into the soil, but who, nevertheless, like the look of a garden and will take a stroll in the outdoors on a sunny day.